Exploring the association between consumption of different types of beverages and erectile dysfunction in US men: evidence from NHANES 2003–2004 data - Wu, Liwei; Li, Bing; Zhou, Hang; Liu, Xiaoqiang (The aging male, 2025)
The aim of this study was to examine the relationship between the type/frequency of consuming beverages and ED among men in America. We used data on erectile function and the frequency of beverage consumption from the National Health and Nutrition Examination Survey (NHANES) 2003-2004. Associations between ED and beverage consumption were analyzed using univariate and multivariate logistic regression. We also stratified by age and adjusted for potential confounders using propensity score matching (PSM). After fully adjusting for covariates, logistic regression showed that regular grape juice consumption (≥ 5 times/week) was related to a lower prevalence of ED (OR = 0.21, 95% CI: 0.08-0.54, = 0.001). Subgroup analyses found that this correlation remained significant for those over 40 years of age (all < 0.05). After PSM adjustment, the association between grape juice consumption and ED remained statistically significant (OR = 0.12, 95% CI: 0.03-0.44, = 0.001). Various beverage types, encompassing tomato, orange, apple, pineapple, and lemonade juices, as well as soft drinks, exhibited a correlation with ED in the initial univariate regression analysis. In men, regular intake of grape juice (≥ 5 times/week) was associated with a lower prevalence of ED, which was particularly significant in men over 40 years of age.